Aisar Engineers Sdn. Bhd. / Nur Ashikin Rozamri - Rozamri, Nur Ashikin (Faculty of Civil Engineering, 2017)
The company that I worked during my internship training is Aisar Engineers Sdn. Bhd. No. 34-A, Jalan TKL 6, Taman Kota Laksamana, Seksyen 1, 75200. Melaka. The chain business of Aisar Engineers is to provide a service for the costumers for drafting and design the structure of construction. My training and internship program been divided into part and phase that had been arranged by the company like example drafting and designing. The purpose of the training is to expose ourselves to various aspects of industrial practices and ethics and also to appreciate the significance of theoretical knowledge gained in the university into the engineering practices. This industrial training program has also help strengthen my professional skills and interpersonal relationship in a professional setting. All these valuable experiences that I had gain from this program will definitely help me to improve myself and develop to become a much better and knowledgeable engineer in the future.